2018
DOI: 10.21467/ias.6.1.28-34
|View full text |Cite
|
Sign up to set email alerts
|

Phytominerals and Phytochemical Studies of Azadiracthta indica, Leea guineensis and Parkia biglobosa Leaves

Abstract: Medicinal plants have great importance in African medicine and are also used as precursors in drug discovery. The medicinal value of plants lie in their bioactive constituents which usually allow them to fight against several diseases. Plant-based natural constituents can be derived from any part of the plant like bark, leaves, flowers, roots, fruits, seeds. The mineral and phytochemical analysis of the leaves of Azadirachta indica, Parkia biglobosa and Leea guineensis were investigated. The leaves were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
4
8
0
1
Order By: Relevance
“…The presence of various phytochemical constituents such as alkaloids, cardiac glycosides, flavonoids, phenolics, saponins, tannins in the L. guineensis fruits reported in this study confirms their therapeutic uses and in conformity with the medicinal properties of secondary plant metabolites [29]. The result obtained in this study was similar to the reports of Awotedu et al [30]. Alkaloids have been reported as the most potent and therapeutically important of all substances isolated from plants which may explain its use against stomach ache, dysentery, diarrhoea, vomiting, constipation and intestinal worms [31].…”
Section: Phytochemical Compositionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of various phytochemical constituents such as alkaloids, cardiac glycosides, flavonoids, phenolics, saponins, tannins in the L. guineensis fruits reported in this study confirms their therapeutic uses and in conformity with the medicinal properties of secondary plant metabolites [29]. The result obtained in this study was similar to the reports of Awotedu et al [30]. Alkaloids have been reported as the most potent and therapeutically important of all substances isolated from plants which may explain its use against stomach ache, dysentery, diarrhoea, vomiting, constipation and intestinal worms [31].…”
Section: Phytochemical Compositionsupporting
confidence: 90%
“…According to the report of Lewis and Elvis-Lewis [33], saponins have been reported to have anti-inflammatory and cardiac depressant properties and restrain growth of carcinogenic cells, without necessary destroying the normal cells in the process. Phenol possesses anti-bactericidal and antimicrobial properties which have shown to exert preventive activity ISSN: 2456-7132 Available online at Journals.aijr.in against infectious and degenerative diseases, inflammation and allergies through antioxidant, antimicrobial and proteins [30]. Steroids are of great importance in the pharmaceutical industry due to its function as sex hormones [34].…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…Medicinal plants always contain some active substances that have been widely reported to contribute their metabolic, physiologic and protective effects to humans [EDEOGA & ERIATA, 2001]. The result obtained in this study corroborates the one reported for Leea guineensis leaves by AWOTEDU & al. (2019), except for the absence of steroids and phlobatanins.…”
Section: Phytochemical Compositionsupporting
confidence: 89%
“…The leaves of L. manillensis are combined with other medicinal recipes for a cutaneous bath. In Nigeria, leaf decoction is used for a variety of uses and medications such as pregnancy detection and immunity booster, as well as treatment for gastroenteritis, enlarged spleen, scurvy, rheumatism, malaria, abdominal pain, diarrhea, and other diseases and infections caused by bacteria and viruses (Awotedu et al 2019(Awotedu et al , 2020Okafor and Ham 1999;Falodun et al 2007;Jiofack et al 2010;Neji et al 2017.…”
Section: Local Medicinal Usesmentioning
confidence: 99%
“…Subsequently, Neji et al (2017) found antimicrobial activity of the stem bark alcoholic extracts against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Candida albicans, Pseudomonas aeruginosa, and Streptococcus pneumoniae (Neji et al 2017). Awotedu et al (2019) recorded the presence of minerals such as potassium, sodium, calcium, phosphorus, magnesium, iron, zinc, manganese, and copper in different quantities. Awotedu et al (2020) further compared the phytochemicals present of L. manillensis leaves using polar and nonpolar solvents.…”
Section: Phytochemistrymentioning
confidence: 99%